The influence of future changes in springtime Arctic ozone on stratospheric and surface climate - Friedel, Marina; id_orcid:0 000-0001-7739-4691; Chiodo, Gabriel; id_orcid:0 000-0002-8079-6314; Seeber, Svenja; Stenke, Andrea; id_orcid:0 000-0002-5916-4013 (ETH Zurich, 2023)
This dataset contains simulation data spanning the 21st century following a high emission scenario (RCP8.5) performed with the two chemistry-climate models SOCOL-MPIOM and WACCM4. It contains two different simulation setups: one with fully interactive chemistry (RCP8.5), and a second setup for which atmospheric ozone has been fixed to a present day (2005-2020) ozone climatology (RCP8.5_fO3). Five ensemble members are available for each setup and model.